The winter's tale [Zimný príbeh anglicky] - Shakespeare, William, 1564-1616; Shakespeare, William, 1564-1616.; Macaw Books (Leicester : Sweet Cherry Publishing, 2020)
"The Winter´s Tale" is one of the Shakespeare´s most popular comedies. The play was first published in 1623, and has since been performed worlwide with a great success. It is set in Sicily, and revolves around the main character, King Leontes, who is consumed by doubts and his wife loyalty. Jealousy drives him to plot his best friend´s murder, imprison his wife and disown their unborn child. The play stretches over a period of sixteen long years during which Leontes realises his mistakes, and he is finally reunited with his estranged wife and daughter.
A short narrative version of the play has been suitably adapted to help to introduce the play to young readers.
Keywords: Sicily (Italy) -- Pictorial works -- Juvenile fiction. -- Kings and rulers; Children's stories -- Pictorial works; čítam si sám (7+); cudzojazyčná literatúra